SYNTHESIS, CHARACTERIZATIONS, AND ADSORPTION PERFORMANCE OF CROSS LINKED POLYMERIC IONIC LIQUID FOR DYES REMOVAL - RAFIQ, REHAN (2020)
Textile manufacturing is one of the core industries which dischargeslarge contents of dyes through aqueous effluents leads to both environmental and economic concerns. Currently,many studiesfor dye removal havebeen examinedsuch as adsorption, membrane filtration, coagulation orflocculation,chemical precipitation, biological treatment,etc.Recently ionic liquids (ILs) have been effectively used fordye removal. However ionic liquids are suffering from issuessuch as high amount usage, liquidity,and miscibility. In contrast to thatpoly (ionic liquids)(PILs) composed ofIL monomers having relatively high stability, high density, and flexibility in structural tuning exhibit superior properties e.g porous structure and easy separation for efficient dye removal.